Stabilisasi Kelembagaan Koperasi Desa Melalui Implementasi Sistem Akuntansi Digital Terintegrasi Sesuai Permenkop UKM No. 2 Tahun 2024 - Pebriani, Reny Aziatul; Yustini, Tien; Frastuti, Melia; Merdekawati, Eka (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Village cooperatives are a vital pillar in strengthening community economics, but many cooperatives still face management challenges, particularly in administrative and accounting aspects. This activity is carried out to provide solutions for the weakness of cooperative institutionalization through the implementation of an integrated digital accounting system that refers to Permenkop UKM No. 2 of 2024 on Cooperative Accounting Standards. The activity's partner is Village Cooperative Limau, which has not yet implemented modern financial recording. The activity will be implemented in Limau Village in August 2025 with 20 participants consisting of cooperative managers, village apparatus, and community members. The activity methods include cooperative regulation awareness campaigns, training on digital accounting-based applications, workshops on cooperative financial report preparation, and system implementation support. The activity results show an 78% increase in participants' understanding of cooperative accounting, an 85% improvement in practical digital recording skills, and the formation of financial recording SOPs compliant with Permenkop No. 2 of 2024. Additionally, the cooperative now has a digital transaction database and a simple financial report format. This activity proves that the implementation of a digital accounting system can strengthen village cooperative institutionalization and improve transparency, accountability, and the cooperative's readiness for digitalization.